The relationship between goal orientations and coping strategies among athletes / Nur Asyikin Mohd Faridz - Mohd Faridz, Nur Asyikin (2013)
Psychological aspect such as goal orientations and coping strategies are crucial to athletes in order to perform well in sport competition. The objectives of the study were to determine goal orientations and coping strategies among athletes based on selected demographic variables of gender, types of sport and level of sport participated. The study was also evaluated the relationship between goal orientations and coping strategies. Athletic Coping Skill Inventory-28 (ACSI) and Task and Ego Orientation in Sport Questionnaire (TEOSQ) were administered to 217 Bukit Jalil Sport School’s athletes age ranged 13 to 19 years old to evaluate the differences of goal orientations and coping strategies among athletes. The results based on Independent T-Test showed that, there were no significant difference on task orientation among athletes based on gender, types of sport and level of sport participated but ego orientation was reported to be significant difference according to these variables. In coping strategies, the demographic variables of gender, types of sport and level of sport participated demonstrated a variety of results for each subscales of coping strategies. Then, a Pearson Correlation reported there were significant relationships between task orientation with all subscales of coping strategies except freedom from worry and there were significant relationships between ego orientations with four subscales of coping strategies except coachability, concentration and freedom from worry. Based on the current results, it is recommended that coaches use the findings to design appropriate programmes to help athletes strengthen coping strategies and other mental aspect in order to enhance their sport performance.